การออกแบบโลจิสติกส์ภายในสำหรับการผลิตอาหารกระป๋องโดยใช้เทคนิคการจำลองสถานการณ์ - กิตินันธ์ มากปรางค์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research was to study a production line of canned fruits at one factory in Chiang Mai as a case study. The objective of this work was to design internal logistics and determine line balancing of canned fruits production line. Motion study was used to analyze the existing production line. Improvement solutions were proposed based on ECRS concept. Moreover, the optimal configuration can be set including location of each work station, balanced work flow, practical working step and optimal number of workers for each station. After that, conveyor system was designed for this production line. Parameters of conveyor system including type, location, size and speed were calculated and evaluated using simulation technique. Finally, break even point and payback period were calculated for economically evaluation. The proposed system (ECRS combine with line balancing) was designed to employ with 41 workers reduced from 56 workers comparing with the current production line. The number of workers reduced a effect on 27% labor cost reduction. When conveyor system was proposed total distance can be reduced to 8.6 meters from 16.49 meters (47.85%) and total time was reduced to 45.87 minutes from 67.07 minutes. Brake even point of the conveyor system was to produce 199,543 units per year. And payback period as 2 months.